2009
DOI: 10.1209/0295-5075/88/27003
|View full text |Cite
|
Sign up to set email alerts
|

Internal chaos in an open quantum system: From Ericson to conductance fluctuations

Abstract: The model of an open Fermi-system is used for studying the interplay of intrinsic chaos and irreversible decay into open continuum channels. Two versions of the model are characterized by one-body chaos coming from disorder or by many-body chaos due to the inter-particle interactions. The continuum coupling is described by the effective non-Hermitian Hamiltonian. Our main interest is in specific correlations of cross sections for various channels in dependence on the coupling strength and degree of internal ch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
30
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 42 publications
3
30
0
Order By: Relevance
“…A typical antiphased behavior of the two types of correlations, first predicted in Ref. [6], is clearly shown. One of the main challenges to study correlations between different transmission channels was to take into account the role of absorption which inevitably occurs in the experimental set up.…”
supporting
confidence: 61%
See 2 more Smart Citations
“…A typical antiphased behavior of the two types of correlations, first predicted in Ref. [6], is clearly shown. One of the main challenges to study correlations between different transmission channels was to take into account the role of absorption which inevitably occurs in the experimental set up.…”
supporting
confidence: 61%
“…In Ref. [6], using Random Matrix Theory (RMT), it was shown that channel correlations strongly depends on the coupling strength between the external environment and the disordered system and on the type of correlations considered (C Σ , C Λ ). In Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Many results turn out to be common for nuclear physics and condensed matter physics of disordered materials [48]. Here I limit myself with few references [49][50][51][52][53][54][55][56].…”
Section: Resultsmentioning
confidence: 99%
“…The method we use here has originally been developed for the description of nuclear reactions [32,33] with many later applications for different open mesoscopic systems ranging from universal conductance fluctuations [34] to electron transport through 1D solid state nanostructures [35,36](see review paper [37] and references therein).…”
Section: Introductionmentioning
confidence: 99%